2003
DOI: 10.1002/ejic.200300072
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Molecular Modelling Studies on the Solution Structure of the InIII−Bleomycin A2 Complex

Abstract: The solution structure of the In III −bleomycin A2 complex (InBLM) has been determined by NMR studies in combination with molecular modelling. Our data indicate that BLM is coordinated to In III through five nitrogen ligands in a distorted tetragonal pyramid configuration. The stability and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…BLM provides five or six ligands for binding to the iron. Because no crystal structure exists, current knowledge of the Fe−BLM structure is based on spectroscopy, molecular dynamics modeling, density functional calculations, , and studies on BLM complexes with Co, Cu, , and other metals. All studies agree on five nitrogen-based ligands (indicated in bold in Figure ). The four equatorial ligands are generally accepted to be an imidazole nitrogen, a deprotonated amide, a pyrimidine nitrogen, and the secondary amine functionality of the β-aminoalanine.…”
Section: Introductionmentioning
confidence: 99%
“…BLM provides five or six ligands for binding to the iron. Because no crystal structure exists, current knowledge of the Fe−BLM structure is based on spectroscopy, molecular dynamics modeling, density functional calculations, , and studies on BLM complexes with Co, Cu, , and other metals. All studies agree on five nitrogen-based ligands (indicated in bold in Figure ). The four equatorial ligands are generally accepted to be an imidazole nitrogen, a deprotonated amide, a pyrimidine nitrogen, and the secondary amine functionality of the β-aminoalanine.…”
Section: Introductionmentioning
confidence: 99%
“…In III ·bleomycins. [22,23] After minimizing the energy of the initial models without any constraints, a molecular dynamics run was performed while increasing the temperature from 300 to 1000 K. The distance constraints were then gradually introduced and after allowing the system to overcome any potential energy minima, the temperature was decreased to 300 K. From the final 20 ps of the molecular dynamics run (at 300 K with distance constraints) 100 structures were collected and were superimposed by massweighted rms fittings of all heavy atoms excluding the bithiazole and C-terminal groups. Their coordinates were averaged and the final model was subjected to energy minimization until the rms gradient became less than 0.01.…”
Section: Molecular Modelling and Structure Determinationmentioning
confidence: 98%
“…Their degeneration owning to the fast rotation around the CϪN bond indicates that the primary amine is not coordinated, in contrast to Ga III and In III ·bleomycins for which two strongly coupled signals had been detected. [22,23] Additionally, four pair of signals strongly coupled to each other were assigned to the pyrim-idine ring PϪNH 2 (δ ϭ 7.51, 7.60), PϪCONH 2 (δ ϭ 7.08, 7.69), AϪCONH 2 (δ ϭ 6.93, 7.21) and MϪCONH 2 (δ ϭ 6.16, 6.61). The pyrimidine amine exhibits only mediumsize NOEs with the neighbouring methyl group, in accordance with previous NMR studies.…”
Section: Assignment and Analysis Of The Nmr Spectramentioning
confidence: 99%
See 1 more Smart Citation